2017
DOI: 10.1186/s12879-017-2617-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing week 2015: lowering barriers for HIV testing among high-risk groups in Amsterdam

Abstract: BackgroundEvaluation of the HIV Testing Week (HTW) 2015 in Amsterdam: the number of (positive) tested persons, characteristics and testing history of the tested population, the differences in attendance per location and the healthcare workers’ experiences and opinions concerning the HTW.MethodsThe HTW took place from 28 November till 4 December 2015. Anonymous HIV rapid testing (INSTI™ HIV1/HIV2 Ab test or Determine™ HIV-1/2 Ag/Ab test) was offered free of charge at four hospitals, 12 general practitioner (GP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…In 5 studies that have evaluated some digital innovations, we observed a few limitations in their offer of services that impacted the process. A Dutch study evaluated a Web-based strategy, where participants could purchase self-tests and access self-test instructions and counseling, but they did not provide data or information on linkages [27]. Of 4 US studies, 2 reported positive findings on the feasibility of use of a kiosk tablet for HIV self-testing in emergency rooms but reported poor engagement (50%) of participants and limited data on detection and linkages [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In 5 studies that have evaluated some digital innovations, we observed a few limitations in their offer of services that impacted the process. A Dutch study evaluated a Web-based strategy, where participants could purchase self-tests and access self-test instructions and counseling, but they did not provide data or information on linkages [27]. Of 4 US studies, 2 reported positive findings on the feasibility of use of a kiosk tablet for HIV self-testing in emergency rooms but reported poor engagement (50%) of participants and limited data on detection and linkages [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The populations in the selected studies were migrants from SSA, NEA and SSA, living in high-income countries with universal health coverage. Of the 16 studies, four were conducted in Australia [46,52,53,54], three each in the Netherlands [44,47,50], Canada [55,57,58] and Italy [45,48,49] and one study in Spain [43], New Zealand [51] and Germany, respectively [56]. Of the 16 studies, two used qualitative methods [51,58].…”
Section: Resultsmentioning
confidence: 99%
“…Individual interventions consisted of clinical interventions, such as testing, vaccination and treatment uptake or adherence. Of the 16 included studies, eight studies reported interventions regarding testing of STIs and uptake of HBV vaccinations [43,44,45,46,47,48,49,50]. Interventions were categorized by method used to encourage testing and vaccination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Bartelsman et al . documented that the HIV testing rate was as low as 32.7% among MSM in Amsterdam 18 . In contrast to other studies, much higher proportions of YMSM and YFSW from current study had been tested for HIV in the past.…”
Section: Discussionmentioning
confidence: 99%